Interactions about Coping - Social Support during Pandemics by Brazilian Users: A Media Analysis Study - Margareth Santos Zanchetta; Vanessa; Stephanie; Janaina Soares; Edwaldo; Marcelo Medeiros (Universidade Federal de Santa Maria, 2023)
Objective- Explore how the Brazilian online community mobilized its own coping resources during the COVID-19 pandemic to deal with mass vaccination concerns, manage and cope with personal stressors brought on by the pandemic, and seek social support. Method- The Canadian Population Health Promotion Model and the Transactional Model of Stress and Coping framed this media content analysis focusing on a socially impactful event: the authorization of COVID-19 vaccinations in Brazil. Results- The retrieval of posts (January-May 2021) found 488 contents distributed as modus operandi (n=117; 24%), coping strategies focused on emotion (n=175; 35.8%), on problem (n=40; 8.1%), on reflection (n=67; 13.7%), and offer of social support (n=89; 18.2%). Among the top-five (n=393; 80.5%) actions and coping strategies, 255 contents about coping strategies with a predominant discourse on emotion-focused coping (n=160; 63.2 %). Conclusion- Interactions sustained a feeling of connection and created a context for belonging, support, and motivation.